Reconciling Systolic Blood Pressure Intervention Trial with Eighth Joint National Commission: a nuanced view of optimal hypertension control in the chronic kidney disease population. Issue 1 (January 2022) - Tantisattamo, Ekamol; Hamiduzzaman, Anum; Sohn, Peter; Ahdoot, Rebecca; Hanna, Ramy M.
Abstract : Purpose of review: Universally lowering blood pressure (BP) may adversely affect some populations especially in the older population. Recent landmark trials revealed cardiovascular benefits of tight controlling systolic BP (SBP) more than several recent BP targets. Implementing the evidence from the studies and guidelines in some populations is reviewed. Recent findings: Eighth Joint National Commission (JNC-8) on hypertension issued conservative guidelines that provided an evolutionary change to BPcontrol in the elderly. However, intensive BP control with SBP < 120 mmHg in Systolic Blood Pressure Intervention Trial (SPRINT) focuses on the improvement of cardiovascular and cerebrovascular outcomes. Although increasingly guidelines are trending toward the SPRINT results, it is noteworthy that not all populations show a favorable outcome with intensive BP control given hypotensive risks to memory, kidney function, orthostasis, and morbidity risks. Summary: Some populations may benefit from implementing the more intensive SBP target, whereas others such as elderly hypertensive patients may benefit from a more liberal SBP target. In the spirit of ' Primum non Nocere', we call for and suggest that a marriage of both SPRINT and JNC-8 recommendations be undertaken to champion the most cardiovascular protections for the greatest number of patients possible whereas preventing complications in vulnerable populations such as the elderly. Among the chronic kidney disease (CKD) population, SBP < 120 mmHg may not necessarily lead to favorable CKD outcomes.